2006
DOI: 10.1016/s1028-4559(09)60188-1
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Chromosome Aberrations in the Second Trimester Using Genetic Amniocentesis: Experience During 1995-2004

Abstract: For daily practice, our data could offer a database for proper genetic counseling, such as termination issues and future pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
34
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 3 publications
5
34
2
Order By: Relevance
“…We found that the most prominent indicator for amniocentesis was the maternal age. This is in accordance with the findings of Yang et al (7), but in contrast to the finding of some other authors who found that the most prominent indicator for amniocentesis was an abnormal maternal serum-screening test or abnormal ultrasound findings (6,8,9).…”
Section: Discussion:-supporting
confidence: 92%
“…We found that the most prominent indicator for amniocentesis was the maternal age. This is in accordance with the findings of Yang et al (7), but in contrast to the finding of some other authors who found that the most prominent indicator for amniocentesis was an abnormal maternal serum-screening test or abnormal ultrasound findings (6,8,9).…”
Section: Discussion:-supporting
confidence: 92%
“…In the 1980s amniocentesis was used primarily for those in advanced maternal age groups, at least 35 yr old. So far, other recent reports have still shown that prenatal diagnosis of chromosomal disorders has been performed mainly for pregnancies at an advanced maternal age [8,9]. This study found Sung-Hee Han, Jeong-Wook An, Gyu-Young Jeong, et al…”
Section: Discussionmentioning
confidence: 57%
“…(2.9%) [9]. A number of cases varies in many studies but, to our knowledge, this study constitutes the largest report in (319 cases), 2.5% (9 cases), and 8.6% (31 cases), respectively.…”
Section: Discussionmentioning
confidence: 58%
“…Up until now, reports from other countries have still shown that prenatal diagnosis of chromosomal disorders is performed mainly for gravidas of an advanced maternal age. For example, as reported in the results of a study of 7028 cases by Tseng et al (2006), AMA was the most common indication for AS. In a larger study from Korea, which included 31,615 cases of mid-trimester AS, abnormal MSS results were reported to be the most common indications for AS since 1994, followed by AMA and abnormal ultrasonographic findings (Han et al, 2008).…”
Section: Discussionmentioning
confidence: 81%
“…The results of prenatal diagnosis of AS, consisting of various numbers of cases, have revealed that the incidence of fetal chromosomal abnormalities ranges between 1.0 and 6.7% (Simpson et al, 1976;Karaoguz et al, 2006;Tseng et al, 2006), higher than the incidence of chromosomal disorders in live newborns (0.5%; Cerrillo Hinojosa et al, 2009). However, this study found that 206 of 2500 cases (8.24%) had chromosomal abnormalities, a result that was higher than previously reported.…”
Section: Discussionmentioning
confidence: 99%